The Water Quality Issue: A Study of Tasik Kemajuan’s Water Quality Status - Muhammad Hafiq Afifi Azman; Rafidah Hamdan; Zarina Md Ali; Zuhaib Siddiqui; Muhammad Aliff Iman Shamsudin (International Journal of Integrated Engineering, 2025)
Lakes are crucial for irrigation, drinkable water, transportation, and power generation. Tasik Kemajuan, located on UTHM's main campus, is used for kayaking and flood mitigation. However, pollution in the lake, through various contaminants, poses risks to human health and the aquatic environment. This study aims to monitor water quality and determine the Water Quality Index (WQI) of Tasik Kemajuan. Six water parameters were evaluated to calculate the WQI: BOD5, COD, TSS, pH, AN, and DO. These parameters contributed to determining the water quality subindex and, ultimately, the WQI based on the formula used in Malaysia. An average water quality status was determined for each parameter: AN at 0.56 mg/L (Class III), BOD5 at 9.75 mg/L (Class IV), COD at 21.93 mg/L (Class IIB), DO at 4.02 mg/L (Class III), pH at 6.45 (Class II), and TSS at 20.33 mg/L (Class I), with the water temperature recorded at 28.50°C (Class IIB). The findings reveal that the WQI for Tasik Kemajuan is on the upper edge of being polluted, with a score of 74, placing it in the Class III category. According to the NWQS, Tasik Kemajuan fails to meet the standards for recreational activities involving direct contact with water and shows that significant purification efforts are necessary to make the water suitable for such purposes.